Socio-Juridical Analysis on Polygamy Requirements in the Compilation of Islamic Law (KHI) - Widiani, Ah. Kholish Hayatuddin Desti (Universitas Islam Negeri Raden Intan Lampung, 2022)
Abstract: Socio-Juridical Analysis on Polygamy Requirements in the Compilation of Islamic Law (KHI).This study is aimed at seeing the relevance of the requirement for polygamy in Law no. I of 1974 concerning marriage and in the Compilation of Islamic Law (KHI) including its implementation in several decisions on polygamy cases in the Religious Court (PA) of Ex Surakarta Regency. This type of research is field research using a socio-juridical approach. The results of this study conclude: 1) The requirements for polygamy as regulated in Law no. I of 1974 and KHI are complementary. While Law no. I of 1974 in article 5 specifies five conditions for polygamy, KHI mentions only three conditions. 2) In general, the reasons put forward by husbands for polygamy are always related to the condition of the wife who is unable to carry out her obligations. 3) Judges, in deciding polygamy cases, do not only base the reasons put forward by the husband but also make other considerations, especially related to matters of the benefit and welfare of the applicant’sfamily